Dietary folate, one‐carbon metabolism‐related genes, and gastric cancer risk in Korea. Issue 2 (17th November 2015) - Kim, Woori; Woo, Hae Dong; Lee, Jeonghee; Choi, Il Ju; Kim, Young Woo; Sung, Joohon; Kim, Jeongseon
Abstract : Scope: We evaluated the interactions between polymorphisms involved in one‐carbon metabolism‐related genes and dietary folate intake in gastric cancer risk within the Korean population through a hospital‐based case‐control study. Methods and results: A total of 542 controls and 271 cases were included. Genotype data were selected from data produced by the Affymetrix Axiom ® Exome 319 Array. We considered seven single nucleotide polymorphisms (SNPs) of five genes whose SNPs are located in the coding region with a minor allele frequency > 5%: MTHFR (G1793A, A1298C, C677T), MTR A2756G, MTRR A66G, SHMT1 C1420T, and SLC19A1 G80A. Our study found that MTR A2756G was associated with a decreased gastric cancer risk. MTHFR G1793A showed a statistically significant interaction between dietary folate intake and gastric cancer. Conclusion: Our results suggest that MTR A2756G is significantly associated with gastric cancer risk, and that MTHFR G1793A statistically interacts with dietary folate intake. Our findings indicate that gene–folate interactions may contribute to gastric cancer risk.